HUBUNGAN ANTARA KADAR SEROTONIN SERUM DENGAN FUNGSI KOGNITIF PADA PASIEN NYERI KEPALA TIPE TEGANG KRONIS - Ega Primadona,* Dwi Pudjonarko,* Dani Rahmawati,* Endang Kustiowati,* Herlina Suryawati,* Trianggoro (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION CHRONIC TENSIONTYPE HEADACHE CTTH IS A MAJOR HEALTH PROBLEM ALTHOUGH THE PREVIOUS DATA IS VERY LIMITED ESPECIALLY IN INDONESIA COGNITIVE DISORDERS OFTEN OCCUR IN CTTH PATIENTS IN ADDITION STRESS FACTORS MENTAL OR PHYSICAL ANXIETY DEPRESSION TEMPERAMENTAL INSTABILITY THAT IS BIGGER EMOTIONAL STATUS ARE FACTORS THAT CAN CAUSE CTTH SEROTONIN IS INVOLVED IN VARIOUS BEHAVIORAL FUNCTIONS ESPECIALLY IN THE REGULATION OF MOOD AGGRESSIVENESS AND IMPULSIVENESS